TREATING ULCERATIVE COLITIS WITH MEDICINAL PLANTS AND INVESTIGATING THE QUALITY OF LIFE OF PATIENTS (World Bulletin of Public Health, 2025)
The fact that many contemporary treatments for ulcerative colitis use medicinal plants in addition to basic medications explains the significance of diagnosing the condition in traditional medicine. This article also discusses how SF36 and IBDQ32 surveys can be used to examine the quality of life of patients.
Keywords: ulcerative colitis; SF-36; IBDQ-32